On Fourier algebra of a locally compact hypergroup - Kalyuzhnyi, A. A.; Podkolzin, G. B.; Chapovsky, Yu. A. (Methods of Functional Analysis and Topology, 2015)
We give sufficient conditions for the Fourier and the Fourier-Stieltjes spaces of a locally compact hypergroup to be Banach algebras.